Peningkatan Ekonomi Desa melalui Pariwisata: Memahami Regulasi dan Manfaatnya - Febriani, Dita; Pebiyan, Anggita; Ali. A, Muh. Daud; Violeta, Fadinda Rishtey; Kalina. L, Ratu Putria (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The Smart Village program aims to enhance community welfare through the application of technology and innovation. In Curahdami village, low literacy and competency levels, particularly among ex-ODGJ (people with mental disorders), are due to low productivity and insufficient skill development support. Social stigma, lack of motivation, and minimal family attention exacerbate this situation, while social disparities limit access to essential services. To address these issues, an empowerment program for ex-ODGJ was designed through the